PENGARUH WORK FAMILY CONFLICT TERHADAP STRES KERJA DAN KEPUASAN KERJA - Metta Astari, Ni Made; Sudibya, I Gde Adnyana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.07.TAHUN 2018DO - 10.24843/EEB.2018.v07.i07.p05, 2018)
In this modern era, the phenomenon of husband and wife who both work to meet the needs of households are common. But not infrequently, this condition actually causes problems in the household. On the other hand, SPG is also faced with Job Demands. In carrying out its duties, an SPG is also required to achieve sales targets that have been determined by the company. Research conducted at PT. Arina Multikarya Denpasar which is one of human resourceservice company in Denpasar. AMK currently has 630 employees and research respondents focused on employees who are married status, as many as 100 people SPG because they tend to experience work family conflict and work stress that impact on job satisfaction. Based on the results of research on SPG PT. AMK Denpasar, we found that work family conflict has a significant positive effect on job stress, job stress has a significant negative effect on job satisfaction, work family conflict has no effect on job satisfaction, and work stress can mediate the influence of work family conflicton job satisfaction.